2023
DOI: 10.18178/ijiet.2023.13.4.1844
|View full text |Cite
|
Sign up to set email alerts
|

A Digital-Analogical Intervention Program Following a Play-Based Approach for Preschoolers: The Effects on Executive Functions and ADHD Symptoms in a Pilot Study

Abstract: Today, the effective use of technological tools is a fundamental aspect of learning. Nevertheless, in Italy’s education system the integration of digital technologies in a pedagogically meaningful way is still not very widespread, especially in non-compulsory levels, such as preschool. Integration of digital technologies as early as preschool could be useful to support child development, especially for fostering executive functions (EFs). These play an important role in the daily life of all children, whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This is consistent with findings reported in the literature, which suggest that pre-school digital-native children are very attracted and motivated by apps, a means they find very familiar and intuitive (24). Furthermore, the study findings also confirmed the capacity of educational apps to enhance WMC and EFs in an intervention program (21,48). This is also in line with studies involving children with ASD, which highlight the added value of using digital technologies during the intervention (14), in particular when seeking to enhance cognitive abilities such as WMC and EFs (4).…”
Section: Key Positive Aspects Of the Interventionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with findings reported in the literature, which suggest that pre-school digital-native children are very attracted and motivated by apps, a means they find very familiar and intuitive (24). Furthermore, the study findings also confirmed the capacity of educational apps to enhance WMC and EFs in an intervention program (21,48). This is also in line with studies involving children with ASD, which highlight the added value of using digital technologies during the intervention (14), in particular when seeking to enhance cognitive abilities such as WMC and EFs (4).…”
Section: Key Positive Aspects Of the Interventionsupporting
confidence: 91%
“…The study in question was carried out as part of the ShareFUN project. 1 This follows the authors' previous research (21), which has demonstrated that the integration of digital and analogical materials in interventions for preschool children could yield added value; this is because the two forms offer different affordances in clinical intervention contexts (22). For the digital activities, we opted for educational apps because they are low cost, familiar, and intuitive for pre-schoolers to use (23).…”
Section: Introductionmentioning
confidence: 91%